Price Risks and the Lead-Lag Relationship between the Futures and Spot Prices of Soybean, Wheat and Corn - Liu, Kai; Koike, Atsushi; Mu, Yueying (Asian Journal of Economic Modelling, 2020)
Faced that the dynamics of the global economy and international politics has produced price risks in the agricultural commodity markets of some countries, we study the lead-lag relationship between the futures and spot prices and market volatility of staple commodities to help make forecasts and manage risk. We design some indexes – "long-term equilibrium", "power of short-term error correction", " Granger causality", "share of information" and "spillover effect" to quantify the lead-lag relationship. Characteristics of futures prices are analyzed with statistical methods and E-GARCH model. The results suggest that spot prices can incorporate the information in futures prices, and move affected by futures prices. This study also identifies the characteristics of trends such as seasonality and asymmetric volatility, which sheds light on some of the key price risks in these commodity markets. In addition, when a commodity is to be harvested or its price affected by bullish news and policies, regulators and traders should pay more attention to price risks, particularly for types of futures with long-lasting volatility, such as soybeans.